The Influence of Representativeness Bias and Hearding Effect on Investment Decisions in the Capital Market - Ikhsan, Muhammad; Handoko Sakti, Sri; Natser Abdoellah, M; Hendro, Junaidi (Takaza Innovatix Labs Ltd., 2024)
This research aims to explore the influence of representativeness bias and herding effect behavior on rational investment decisions in the capital market. Quantitative methods were used involving 100 investors who were members of the Beginner Stock Investor (ISP) community in Jakarta. The results of the analysis show that representativeness bias and herding effect behavior have a significant influence on rational investment decisions. These findings highlight the importance of awareness of the psychological factors that influence investor behavior in making investment decisions, as well as the need for a more independent and focused approach to fundamental analysis to ensure more appropriate and optimal investment decisions. The practical implication of this research is that a better understanding of investor behavior and its impact on markets can help investors to overcome these biases and improve the quality of their investment decisions.